Pengaruh Etika Bisnis dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan di Auto 2000 Soekarno Hatta Bandung - Yosua Henoch Maraden; Kiagus Muhammad Amran; Asarethka Adjane Annisawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of business ethics and customer satisfaction on customer loyalty at Auto2000 Soekarno-Hatta Bandung. The research method employed is quantitative with a survey approach, involving respondents who are Auto2000 customers. Sampling was conducted using purposive sampling with a total of n respondents. The research instrument was a questionnaire tested for validity and reliability, while data analysis employed multiple linear regression to examine the effect of the independent variables, namely business ethics (X1) and customer satisfaction (X2), on the dependent variable, customer loyalty (Y). The results show that, partially, business ethics has a positive and significant effect on customer loyalty, and customer satisfaction also has a positive and significant effect on customer loyalty. Simultaneously, both independent variables have a positive and significant impact on customer loyalty. The coefficient of determination (R²) indicates that the proportion of the contribution of business ethics and customer satisfaction to customer loyalty is substantial, while the remainder is influenced by other factors outside this study. These findings affirm that implementing strong business ethics principles—such as honesty, transparency, and responsibility—combined with delivering services that meet or exceed customer expectations, is a crucial strategy for building and sustaining customer loyalty in the automotive industry